Removal of Biomass and Nutrients by Weeds and Direct-Seeded Rice under Conservation Agriculture in Light-Textured Soils of North-Western India - Salwinder Singh Dhaliwal (MDPI AG, 2021)
The escalating scarcity of irrigation water, transplantation of rice on light-textured soils and labour cost acted as major drivers for the transition towards direct-seeded rice (DSR) cultivation from the conventionally flooded transplanting system. Despite these advantages, DSR is a challenge in light texture soil due to heavy weed infestation and a slight decline in crop yield. The weeds compete for nutrients and have an adverse effect on the growth and yield of crops. Hence, to assess the removal of macro and micronutrients by weeds and direct-seeded rice, a field experiment was carried out on sandy loam soil for two consecutive Kharif seasons (2018 and 2019). Three treatments from rice, namely: DSR under zero tillage (DSR-ZT), DSR under conventional tillage (DSR-CT) and DSR under reduced tillage (DSR-RT) were taken as main plots with three tillage treatments in wheat, namely: Conventional tillage without rice straw (CTW-R), Zero tillage without rice straw (ZTW-R) and Zero tillage with straw as mulch using Happy Seeder (ZTW+R) as subplots, replicated thrice. Among the rice establishment methods, DSR-RT showed an edge in terms of rice grain and straw yield (6.18 and 8.14 Mg ha−1, respectively) as well as macro- and micronutrient uptake by rice. Under management practices, ZTW+R proved as an efficient strategy in terms of yield and nutrient uptake by crops. The contribution of weeds towards biomass production was maximum under the ZTW-R (9.44%) treatment followed by DSR-ZT (7.72%). The nutrient budgeting showed that macro- and micronutrient removal by weeds was minimum under reduced tillage (24.51 and 50.35%, respectively), whereas it was 21.88 and 44.87% when wheat was grown under conventional tillage without rice straw. In overall, the research study concluded that weeds on an average remove 25.65 % macronutrients (N, P, K) and 51.47% of micronutrients (Zn, Cu, Fe and Mn) in DSR under rice-wheat cropping system.